An Efficient Blade Type Rasper for Cassava Starch Extraction - Sajeev, M.S; Nanda, S.K; Sherriff, J.T (JOURNAL OF ROOT CROPS, 2013)
The cassava tubers, being highly perishable, should be immediately processed into starch or flour for value addition, which enhances the income of farmers resulting in food security and rural employment. Starch is generally prepared by wet extraction process, in which rasping or crushing is an important unit operation for the disintegration of the cell wall and washing out of the starch granules by water. In the commonly used raspers, mild steel sheets with nail punched protrusions are fixed around a wooden drum which rotates inside a crushing chamber to crush the tubers. The loss of sharpness of the protruded sheets necessitated frequent replacement and this increased the cost of processing. Hence a cost effective cassava rasper consisting of a crushing drum of mild steel pipe with high speed blade sets fixed on its circumference was developed and tested for its performance by changing the rasper speed and water inflow rate. Experiments were carried out to extract starch from cassava at different rasper speeds (1000, 1200 and 1400 rpm) and water inflow rates (7, 15 and 23 l min-1). The particle size analysis of the crushed mash obtained from the slurry showed that the volume surface mean diameter was found to be the highest followed by mass mean diameter and volume mean diameter. As the speed of rotation increased, the average particle size decreased, whereas with increase in water flow rate, the particle size increased. Maximum fineness modulus of the crushed mash was 4.82. The capacity of the machine was found to be about 900-1000 kg h-1. The amount of starch extracted was 18.98% giving rise to a starch recovery of 83.39%.